Factors Affecting the Effectiveness of Internal Control in Chinese SMEs: - Feng, Na (Pacific International Journal, 2023)
SMEs represent economic vitality and can reflect the degree of development of a country’s economy; the more developed the economy, the greater the number of SMEs. However, the survival environment of SMEs is complicated, resulting in short life cycle and weak risk resistance. Fortunately, China’s SME business environment is getting better and better. At this time, if SMEs want to survive in the competition and develop in the survival, they just need to improve their own business management and risk prevention ability. And internal control is one of the important management tools and functions to enhance market competitiveness. Internal control for SMEs is equivalent to capillaries for people. Any organ or part of a human being is covered with capillaries, and internal control is also ubiquitous throughout the entire life cycle of SMEs, covering and soaking in all aspects, whether at the strategic level, or at the business level; at the financial level or at the management level; at the start-up stage, or at the growth, maturity and transformation stages; at the governance level, or at the management and business levels; at the sales department, or at the production department; all have internal control. Therefore, internal control in SMEs is no longer a multiple choice question of whether to design and implement, but a must-answer question of how to reasonably design and effectively implement. High quality internal control is not something that can be achieved overnight, nor is it something that is set in stone. In other words, the design and implementation of internal control is a dynamic process of change. The demand and supply factors for internal controls in economic activities and business management are not static, but are constantly changing, and these changes, in turn, often require changes in internal controls. Moreover, internal controls should not be passively accepted, but actively created according to the needs. The question discussed in this study is: What are the practical difficulties in establishing an effective internal control system in SMEs? Based on Maslow’s Hierarchy of Needs Theory and Demand and Supply Theory, and using the interview method, this study interviewed managers of 32 SMEs in China from their business objectives to the five elements of internal control, using the SPADER (Situation, Problem, Alternative, Decision, Executive, Review.) and PDCA (Plan, Do, Check and Act) cycles in operations management and quality management as research ideas. And found that currently all Chinese SME owners have recognized the necessity and importance of internal control to varying degrees, but firstly, they do not know how to do it, secondly, there is not sufficient urgency, and thirdly, it is difficult to realize systematically, in addition, due to financial and capacity constraints, they are not in a condition to give the corresponding resource allocation and investment.